Education on the country's agenda - Iguiñiz Echeverría, Manuel (1993)
In Peru, the issue of education has been intermittently in public attention and debate in recent years. Since Alan García's proposal for municipalization until today, the educational problem has had, albeit sporadically, a place in social and political concern and in the media. Public discussion of educational issues tends to become more frequent. In the area of ​​growing, distressing.